The physiotherapist in primary health care: Perception of patients treated at the physiotherapy outpatient clinic in the municipality of Pinheiros - ES (International Seven Journal of Health Research, 2023)
Introduction: For a long time, Physical Therapy was summarized as rehabilitation, after many discussions, the physical therapist becomes a professional active in prevention and health promotion, starting to be part of primary health care, focusing on analyzing the reports of patients who are treated in primary care and how the applicability of possible methods existing within the profession is being. Objective: The objective of the present study was to analyze the perception of patients treated at the Physical Therapy outpatient clinic in the city of Pinheiros - ES and to see the importance of the professional's participation in this environment. Methodology: This is a quantitative, exploratory and descriptive research, where the main complaints and perception of Physical Therapy patients in the public sector of the city of Pinheiros - ES were studied. Results: It was observed that (56%) of the patients perceive little improvement with the treatment, that (28%) they prefer to receive the physiotherapist at their home, that the physiotherapist always clarifies the patients' doubts (68%), that the patients feel safe with the physiotherapeutic conducts (76%), but that they do not see much improvement with the treatment, (96%) of the patients consider the physiotherapist kind and treats them with respect. Conclusion: It is concluded that the perception of users who undergo Physical Therapy in the public sector is positive, even if they see few improvements in their treatment, due to the few sessions, but it ends up leaving something to be desired in terms of the physical therapist clearly explaining the treatment that will be performed.